Pulmonary sequestration associated with increased serum tumor markers and elevated standard uptake value level in PET/CT: A case report and literature review. Issue 31 (August 2018) - Li, Xiaojun; He, Wenlong; Li, Jinhua; Ouyang, Ruoyun; Chen, Ping; Peng, Hong; Zong, Dandan
Abstract: Rationale: Pulmonary sequestration (PS) is a congenital pulmonary malformation wherein a piece of tissue that ultimately develops into lung tissue is not attached to the pulmonary arterial blood supply, sometimes it is difficult to diagnosis with no specific laboratory tests, discover an abnormal blood supply from aorta by imaging tests is a key step in diagnose. Patient concerns: A 54-year-old male smoker presented with cough, expectoration and blood in the sputum. Diagnoses: Computed tomography (CT) shows lesion in right lung, moderate standard uptake value (SUV) elevation of position-emission tomography/computed tomography (PET/CT) in a part of the lesion, and an increased (1, 3)-β-D-glucan assay (G test), Galactomannan enzyme immune-assay (GM test) and tumor marker level, biopsy of lung in different times produced inconclusive results, then finally diagnose of pulmonary sequestration is made by observing an abnormal blood supply from the thoracic aorta and volume change of mass. Interventions: The patient refused lower lobectomy which is the main treatment of PS. He was discharged with oral hemostatic and was advised to undergo regular medical checkups. Outcomes: The patient has been followed for a year under an outpatient regimen. Symptoms of the cough and expectoration were relieved, however, blood in the sputum remains unchanged. Lessons: It suggests the need for criteria for a thorough diagnostic work-up. It put emphasis on the importance of considering PS as part of the diagnosis of a lesion in the lung disease and underscore the blood supply of mass. Bronchoscopy or pulmonary lobectomy and follow up of the patient are important for patients diagnosed with pulmonary sequestration.